ЧАСТОТНІ ХАРАКТЕРИСТИКИ БЕЗКОНТАКТНИХ МАГНІТО-ЕЛЕКТРИЧНИХ ДВИГУНІВ ЗВОРОТНО-ОБЕРТАЛЬНОГО РУХУ - Акинін, К.П.; Кіреєв, В.Г.; Петухов, И.С.; Філоменко, А.А. (Інститут електродинаміки Національної академії наук України, 2020)
In this paper, the frequency characteristics of a special brushless magnetoelectric motor of return-rotary motion with sinusoidal and rectangular forms of the carrier signal are investigated. The method of generating a feedback signal on the amplitude of the rotor shaft oscillations angle has been improved by fixing the value of the signal at the moment of reaching its amplitude. The method of calculating the control system of the oscillations angle amplitude is investigated based on the frequency characteristics of the open-loop system by setting the phase stability margin. Examples of the calculation of transient processes of regulation of the oscillations angle amplitude and the effective value of the stator current when starting the motor and changing the mechanical load are given. Ref. 9, fig. 6, tables 2.